South Africa-US Contest over Africa Policy Dominance: A Study with Emphasis on AFRICOM, BRICS and Libyan Issues - Rupiya, Martin (The Journal of US Africa -Studies, 2021)
Foreign policy is embodied in the pursuit of national interests by States in their interaction with other countries. The attainment of Nelson Mandela’s African National Congress (ANC) led majority rule statehood and its relationship with the midwife, the United States, provides us with one of the most complex case study examined between the late 1980s until the present. At the end of the Cold War, a period which coincided with the decolonisation of several countries in Southern Africa including Namibia and South Africa, following mediation by the US, Assistant Secretary of State for Africa Affairs, Chester Crocker United States, predicted on its new found relationship with the then United Soviet Socialist Republics (USSR) and its presence in Angola, informed the decolonization of the sub-regional in which the US targeted South Africa’s apartheid regime towards abandoning its military destabilisation activities and providing security guarantees to the white minority community under the new African majority regime. The result was the withdrawal of Cuban forces in Angola, Namibia independence and finally, the ANC led by the long imprisoned Nelson Mandela at the head of the first coalition government. Consequently, this immediate post-independence arrangement constrained the freedom of action of the ANC during its first term in power. In the subsequent era, the evidence reveals tension and clashes of interests between Washington and Pretoria manifest in at least three areas: creating an African coalition during 2006 against US policy preferences such as the deployment of Africa Command (AFRICOM) on the continent; the 2010 entering into an international political economy of BRICS against Washington’s global dominance and finally, the 2011 coalition attempts under the auspices of the African Union (AU) challenge towards Western intervention in Libya and the deposition of Colonel Muammar Gaddafi on 23 October 2011. Based on secondary sources, newspaper, academic thesis and other official reports this article examines the tensions that developed between Washington and Tshwane/Pretoria over their intentions over Africa. This assesses three areas of foreign policy relationships depicting: contestation, belligerence and finally belated confrontation. These phases begin with the 2006 US intention to locate AFRICOM in Africa, a development openly opposed by President Thabo Mbeki through the AU. This is followed by South Africa joining the global economic competitors made up of Brazil, Russia, India, China and South Africa (BRICS) at the invitation by China. This competitive relationship not only challenged the existing World Bank and IMF dominance but created an entry point for China in Africa. Finally, the article examines the US policy on Libya of Colonel Muammar Gaddafi in 2011 after adopting UN Resolution 1973 in a subsequent development that went against the AU and South Africa, culminating in the capture and assassination of Gaddaffi on 23 October 2011. Conclusively, the US-South Africa relationship over Africa has been characterised by phases of belligerence, collegial neutrality and uncooperative behaviour. Key Words: KAFRICOM, BRICS, Foreign Policy; South Africa; United States